P418 Safety and efficacy of olorinab, a peripherally restricted, highly-selective, cannabinoid receptor 2 agonist in a phase 2A study in chronic abdominal pain associated with Crohn's disease. (25th January 2019) - Higgins, P; Ginsburg, D; Gilder, K; Gilder, K; Walsh, B; English, B; Turner, S; Klassen, P; Hanauer, S; Barish, C; Yacyshyn, B
Abstract: Background: Patients with Crohn's disease (CD) often experience abdominal pain despite effective control of inflammation, contributing to opioid and cannabis use. Visceral pain may be modulated by cannabinoid receptors CB1 and CB2, but clinical development of non-selective agonists has been limited by unwanted psychotropic effects from CB1 agonism. Olorinab (APD371) is a peripherally restricted, highly-selective agonist of the CB2 receptor. Olorinab was generally well tolerated without psychotropic effects in healthy volunteers. This study evaluated the effects of olorinab in CD patients with minimal inflammation experiencing abdominal pain. Methods: This randomised, open-label, parallel group, multi-centre Phase 2a study enrolled subjects aged 18–66 years diagnosed with quiescent CD (simple endoscopic score-CD <10 or faecal calprotectin <500 μg/g) experiencing abdominal pain, defined as weekly average abdominal pain score (AAPS; daily pain scores averaged over 1 week) ≥4 on a scale of 0 (no pain) to 10 (worst possible). Subjects were randomly assigned 1:1 to receive 25 or 100 mg oral olorinab 3 times a day (TID) for up to 8 weeks. The primary objectives were safety and tolerability. Efficacy endpoints included change in AAPS from baseline week (BL) to Weeks 4 and 8, change in AAPS from pre-dose to 1.5 h post-dose, and proportion of subjects who were clinical responders (≥30% reduction in weekly AAPS from BL). Results: In all, 14 subjects (57% female, 86% white, mean age of 36 years, 12 on active treatment for CD) were randomised with a mean BL AAPS of 5.6. Eleven subjects with mean BL AAPS of 6.0 provided Week 8 AAPS data. Adverse events (AEs) were generally mild-to-moderate and limited in duration and were reported in 67% (4/6) of subjects who received 25 mg TID and in 75% (6/8) of subjects who received 100 mg TID. No subjects discontinued because of AEs. AEs in ≥2 subjects included drug hypersensitivity, pain in extremity, and hypomagnesaemia. The only 2 serious AEs (pneumonia, worsening interstitial pneumonia) occurred in the same subject and were not considered treatment-related. No clinically significant changes in vital signs or clinical safety lab results were observed. The AAPS was significantly improved from BL at Weeks 4 and 8. Change in AAPS from BL to the time of peak concentration (1.5 h post-dose) during Week 8 was −4.6 on an 11 point scale ( n = 11; p < 0.001). Clinical response in AAPS (≥30% reduction) was seen in 85% (11/13) of subjects with evaluable data at Week 4 and 100% (11/11) at Week 8. Conclusions: Results from this open-label olorinab study provide evidence for an improvement in AAPS without psychotropic effects in subjects with quiescent CD experiencing abdominal pain.